Characterizations of blaCTX–M–14 and blaCTX–M–64 in a clinical isolate of Escherichia coli from China - Yang, Mingxing; Liu, Dong; Li, Xiaoquan; Xiao, Chuting; Mao, Yingge; He, Jiaqi; Feng, Jiao; Wang, Li (Frontiers in Microbiology, 2023)
Extended-spectrum beta-lactamase-producing Gram-negative bacteria are common in the community and hospitals. To monitor ESBLs mediated by the CTX-M genotype, we collected clinical ESBL pathogenic strains from a hospital in central China and observed a strain of Escherichia coli, namely Ec15103 carrying blaCTX–M–14, blaCTX–M–64 and blaTEM–1, isolated from the blood of a 7-day-old infant in 2015. Strain Ec15103 contains two drug resistance plasmids: pEc15103A, an IncFI-type plasmid that cannot be conjugatively transferred and carries the drug resistance genes blaTEM–1, aacC2, aadA5, sul1, mph(A), sul2, strAB, and tetA(A); and pEc15103B, an IncK2/Z-type plasmid that carries the conjugation transfer gene and blaCTX–M–14. In addition, blaCTX–M–64 is located on the chromosome of Ec15103, and it is the first report of pathogen with blaCTX–M–64 located on its chromosome (the search terms used “blaCTX-M-64” and “chromosome”). blaCTX–M–14 and blaCTX–M–64 are carried by ISEcp1-mediated transposon Tn6503a and Tn6502, respectively. The conjugation transfer ability of pEc15103B was significantly inhibited by zidovudine (AZT) and linoleic acid (LA) and that expression of blaCTX–M–14, blaCTX–M–64 and blaTEM–1 at the mRNA level did not change based on the concentration of cefotaxime or ampicillin. Co-occurrence of blaCTX–M–14 and blaCTX–M–64 in a single isolate will enhance the drug resistance of bacteria, and the presence of blaCTX–M–64 in the chromosome may make the resistance more maintain. This fact will facilitate its dissemination and persistence under different antimicrobial selection pressures. It is essential to prevent these strains from further spreading in a hospital environment.